Evaluation of the Physical Activity Level of Elderly Women in the Canton of Sarajevo in Bosnia and Herzegovina - Izet Bajramovic; Dusko Bjelica; Munir Talovic; Haris Alic; Slavenko Likic (Journal of Anthropology of Sport and Physical Education, 2018)
The aim of this study was to determine the level of physical activity of elderly women living in the Canton of Sarajevo in Bosnia and Herzegovina. The sample consisted of 115 subjects, divided in two sub-sample: fi rst group aged 50-59 (54.87 ± 2.59), N = 75; and second group aged 60-69 (64.52 ± 2.80), N = 40. Data collection was obtained using a long version of the International Physical Activity Questionnaires (IPAQ). After the results analysis, a high overall level of physical activity of the treated sample of elderly women was determined. The fi rst group of elderly women (age 50-59) achieved the total work MET 13990.56 ± 11012.0; the second group of elderly women (age 60-69) achieved the total work MET 9921.02 ± 7861.13. Determined exceptionally heavy physical activity (MET) was the most dominant mode of energy consumption in the case of both elderly women groups, was not expected. The fi rst group was more physically active compared to the second group of elderly women (p <0.05). This research has confi rmed that physical activity decreases with age. Promoting physical activity to improve the quality of life of elderly people should be a priority task of health policy of all local communities. It is important to provide appropriate ways of information about the health status of elderly people in order to determine priorities, and accordingly plan appropriate programs of physical activity.